Embedding interagency working between schools and mental health specialists: A service evaluation of the Mental Health Services and Schools and Colleges Link Programme workshops. (October 2019) - Cortina, Melissa A.; Shipman, Judith; Saunders, Felicity; Day, Laurie; Blades, Rachel; Smith, Jaime; Wolpert, Miranda
There is increasing focus on the need for schools to work more effectively with specialist mental health providers, but there have been historic challenges in embedding closer interagency working. This article reports the results of a service evaluation of a 2-day workshop designed to facilitate improved working between schools and children and young people's mental health services (CYPMHS). Mental health leads from 255 schools, mental health professionals and other key stakeholders all took part in one of 26 two-day workshops across the United Kingdom. The impact on interagency working was examined using changes in pre- and post-survey results, changes in self-reported aspects of interagency working and 10 local reviews of practice. The pre–post questionnaires showed improvements in interagency working (e.g. 55% of school leads reported being in 'monthly' or 'continuous' contact with the National Health Service (NHS) CYPMHS 1 at follow-up, compared with 24% at baseline). The group-completed CASCADE framework showed an overall increase in collaborative working, although some areas continued to report significant challenges such as in relation to common outcome measures. The local reviews found positive changes in interagency working, in terms of building relationships, improved communication and sharing good practice. This service evaluation of the workshops found some evidence of improved interagency working between schools and CYPMHS, but more controlled research is needed to consider generalisability and scalability.